Children of the sea. 4 - Igarashi, Daisuke (Viz, 2010)
Jim, Dehdeh, and Ruka's mother locate Anglade's yacht, but the only thing they find is a cryptic invitation for Jim. While Jim tries to figure it out, Ruka's mother reminisces about her daughter, and the changes continue in the seas worldwide.